Mobility and inequality trends - Bandyopadhyay, Sanghamitra; Rodríguez, Juan Gabriel (Research on economic inequality ;, 2023)
Research on Economic Inequality is a well-established publication of quality research. This 30th volume features insightful and original papers from the 9th Society for the Study of Economic Inequality (ECINEQ) meeting. Mobility and Inequality Trends begins by illustrating the trajectory of income inequality in the world over the course of recent decades before the second paper makes a crucial distinction between 'bad' inequality, which is detrimental to society, and 'good' inequality, which is beneficial. Focus then shifts to bad inequality, one paper covering the relationship between intergenerational elasticity and inequality of opportunity, and the second studying the relationship between intergenerational mobility and life satisfaction in Spain. The volume then progresses to defend the use of intermediate views of inequality when constructing indicators of social welfare obtained through the use of average income and the Gini coefficient before investigating the advantage of using a multifaceted approach to income mobility measurement. To conclude Mobility and Inequality Trends presents an intensive exploration of income inequality in China and then studies the effects of the policy measure "Minimum Living Income. Finally, the last paper studies the impact of the COVID-19 pandemic on economic stimulus policies.